2019
DOI: 10.21203/rs.2.13336/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Laryngeal mask airway reduces incidence of post-operative sore throat after thyroid surgery compared with endotracheal tube: a single-blinded randomized controlled trial

Abstract: BackgroundSore throat is a remarkable complication after thyroid surgery with endotracheal tube (ETT). Many studies revealed that laryngeal mask airway (LMA) might reduce the incidence and severity of postoperative sore throat. However, little is known about the use of a flexible reinforced LMA (FLMA) in thyroid surgery. The purpose of this study was to explore the potential benefits of FLMA compared with ETT on postoperative sore throat.MethodsIn this prospective, single-blinded, randomized, controlled trial,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
1
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 9 publications
0
3
1
3
Order By: Relevance
“…Second, the incidence of POST was assessed only at discharge from the PACU. POST may persist for 2 to 3 days and require additional attention from healthcare providers [26]. However, Seet et al found that the incidence of POST was low (3.1%) in their pressure-limiting group at 24 hours postoperatively [4].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Second, the incidence of POST was assessed only at discharge from the PACU. POST may persist for 2 to 3 days and require additional attention from healthcare providers [26]. However, Seet et al found that the incidence of POST was low (3.1%) in their pressure-limiting group at 24 hours postoperatively [4].…”
Section: Discussionmentioning
confidence: 98%
“…It affects patient satisfaction and can in uence activity after discharge. SADs offers an alternative to traditional tracheal intubation, with the potential bene t of reducing the risk of sore throat [5][6][7]. However, the overall incidence of POST after using an SAD can be as high as 42% [8].…”
Section: Discussionmentioning
confidence: 99%
“…Beberapa penelitian menyimpulkan bahwa kandungan asam lemak dalam VCO berpotensi untuk dikembangkan sebagai analgetik, antipiretik, antiinflamasi [10][11][12][13] , sebagai obat untuk menyembuhkan luka bakar, antimikroba, 14 sebagai pelembab untuk melindungi kulit dan mencegah kulit kering, 15 sebagai pelumas untuk mengurangi efek gesekan dan geseran. 16 Manfaat Sehingga keberhasilan pemasangan juga dapat mempengaruhi kejadian nyeri 6,18,20,19,[21][22][23][24][25] Pada jam ke-0 pascaoperasi penelitian ini mendapatkan hasil prevalensi nyeri tenggorok pascaoperasi sebesar 47,6%, Gong et al mendapatkan hasil sebesar 48,5%, dengan menggunakan LMA tanpa lubrikasi. 19 Kiran et al mendapatkan hasil 0% dengan menggunakan LMA yang dilubrikasi dengan betametason gel 0,05% dan 53,3% dengan LMA yang dilubrikasi dengan jeli lignokain 2%.…”
Section: Pendahuluanunclassified
“…16 Manfaat Sehingga keberhasilan pemasangan juga dapat mempengaruhi kejadian nyeri 6,18,20,19,[21][22][23][24][25] Pada jam ke-0 pascaoperasi penelitian ini mendapatkan hasil prevalensi nyeri tenggorok pascaoperasi sebesar 47,6%, Gong et al mendapatkan hasil sebesar 48,5%, dengan menggunakan LMA tanpa lubrikasi. 19 Kiran et al mendapatkan hasil 0% dengan menggunakan LMA yang dilubrikasi dengan betametason gel 0,05% dan 53,3% dengan LMA yang dilubrikasi dengan jeli lignokain 2%. 25 Hasil penelitian ini lebih baik dibandingkan dua penelitian di atas, tetapi tidak lebih baik bila dibandingkan dengan lubrikan betametason gel 0,05%.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation